Low magnetisation alloys for in-plane spin transfer torque devices - COEY, JOHN; OGUZ, KAAN (My University, 2012)
Magnetic properties of thin films of three in-plane alloy systems, namely, Co40Ni40?xCrxB20, Co40Fe40?xNixB20, and Co40Fe40?xCrxB20 are investigated with a view to reducing the critical current density (jc ) for spin transfertorque switching in MgO barrier magnetic tunnel junction nanopillars. In all three systems, the saturation magnetisation, Ms , decreases with increasing Cr or Ni substitution. The Co40Fe40?xCrxB20 alloy system is found to be the best in terms of reducing Ms , while maintaining a high tunnel magnetoresistance ratio. Ferromagnetic resonance experiments revealed that the damping coefficient of CoFeCrB alloy remains unchanged with increasing Cr content, but jc is reduced by a factor of four to 4.9???105?A/cm2 by using a Co40Fe32.7Cr7.3B20 free layer while maintaining a magnetoresistance of around 60 %
PUBLISHED
Keywords: Physics